KOMPETENSI GURU DALAM MENYUSUN RENCANA PROGRAM PEMBELAJARAN HARIAN MELALUI BIMBINGAN BERKELANJUTAN - Emanuel Adrianus Wagu (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
The aim of this school action research was to improve the ability of teachers to prepare daily planning programs. The type of research used in this research is school action research with observation. The activities in this study consisted of action planning, action implementation, observation, and reflection stages. Datacollection techniques using school observation techniques. The observation instrument used is the teacher's ability assessment tool (APKG) in the form of an assessment instrument for preparing the Daily Program Plan. The data analysis used is a comparative descriptive analysis technique. Quantitative data obtained is described in the form of words or explanations. Furthermore, data comparisons were carried out to ensure whether there was an increase in the teacher's ability to plan daily programs. The results of the research show the finding that continuous guidance can increase teacher motivation in preparing a complete RKH. The teacher shows seriousness in understanding and compiling the RKH, especially after receiving guidance on the development/composition of the RKH from the researcher. This information the researchers obtained from the results of observations when conducting interviews and guidance on the development/composition of RKH to teachers. Continuing guidance can improve teacher competence in preparing RKH. This can be proven from the results of observations which show that there has been an increase in teacher competence in preparing the RKH.